ADALIMUMAB INDUCTION AND MAINTAINING REMISSION FOR CROHN’S DISEASE IN PATIENT WHO LOST RESPONSE TO INFLIXIMAB. Case report - Ivaylo Vazharov; Hristo Bozov; Snezha Zlateva; Georgi Bonchev (Journal of IMAB, 2016)
This is a report of 30 years old woman suffering from Crohn’s disease who had a good clinical response to Infliximab (Remicade) at first, but during the treatment after 5 months she lost response. After receiving Adalimumab (Humira) clinical remission was reached on the day 20. The case demonstrates rapid response to adalimumab in incidence of losing efficacy to another tumor necrotic factor - alpha (TNF- alpha) antagonist.